Intervenciones de enfermería en paciente con Insuficiencia renal crónica en niños menores de 15 años - Zambrano Moran, José Jordán (2018)
Chronic renal failure is a disease considered harmful, because it occurs when the kidneys fail to function properly, so it begins when the kidney loses the ability to perform some of its functions such as filtering, absorption, secretion or endocrine, and later it ends up as kidney damage. Patients with this disease have a high rate of morbidity and mortality, most of the cases the kidney damage develops in a hidden and silent way which makes it even more dangerous. The following clinical case that will be carried out is about the nursing intervention in a patient with chronic renal insufficiency in children under 15 years of age, which has as objective to carry out a study to know the causes that cause chronic renal insufficiency. evaluate the treatments and identify the problems and complications. The abnormal excretion of proteins in the urine depends on the type of disease. Low molecular weight globulins are characteristic of some tubulointerstitial diseases, while albuminuria is a very sensitive marker of Chronic Renal Disease in Diabetes Mellitus, Glomerular disease, Arterial Hypertension.